ANALISIS KINERJA SEKTOR PUBLIK (PDAM KABUPATEN MEMPAWAH) MENGGUNAKAN ASPEK KEUANGAN DAN NON KEUANGAN - Pratama, Ade Putri (JAAKFE UNTAN (Jurnal Audit dan Akuntansi Fakultas Ekonomi Universitas Tanjungpura), 2018)
Performance assessment is needed to find out how far the target or results obtained by the company are achieved, and as an ingredient to make improvements or evaluations. In the Minister of Home Affairs Decree No. 47 of 1999 concerning guidelines for evaluating the performance of Regional Water Supply Companies (PDAMs), that indicator in assessing the performance of PDAM performance is seen from three main aspects, namely financial aspects, operational aspects, and administrative aspects. The formulation of the problem in this study is: "How are the results of the PDAM performance measurement using financial and non-financial aspects?"The purpose of this study was to determine the results of PDAM performance using financial and non-financial aspects and provide an alternative in assessing the company's performance appropriately and comprehensively that can be applied to PDAMs. The analytical tool used is the Ministry of Home Affairs Decree Number 47 of 1999 concerning guidelines for evaluating the performance of Regional Water Supply Companies (PDAMs), which assesses the performance of PDAMs using three main aspects, namely financial aspects, operational aspects, and administrative aspects. From the results of the final performance assessment, it is known that in 2014, the company obtained a final score of 43.28 which was in the less category, whereas in 2015, the results of the performance appraisal obtained a final score of 48.60 which was in the sufficient category and in 2016 , the performance appraisal results in a final score of 46.25 and is in the sufficient category. Keywords: Keputusan Menteri Dalam Negeri Nomor 47 Tahun 1999, FinancialAspects, Operational Aspects, and Administrative Aspects